Social Psychology / Eighth Edition - Baron Robert A.; Byrne Donn (Academic Press, 1997)
The Field of Psychology: How We Tink About and Interact with Others, Social Perception: Understanding Others, Social Cognition: Thinking about Others and the Social World, Attitudes: Evaluating the Social World, Aspects of Social Identity: Establishing One's Self and Gender, Prejudice and Discrimination: Understanding Their Nature and Countering Their Effects, Interpersonal Attraction: Initial Contact and Linking and Becoming Acquainted, The Joys and Sorrows of Close Relationships: Family and Friends and Lovers and Spouses, Social Influence: How We Change Others' Behavior and How They Change Ours, Prosocial Behavior: Helping Other People, Aggression: Its Nature and Causes and Control, Groups and Individuals: The Consequences of Belonging, Social Psychology and Society: Legal and Organizational Applications, Social Psychology in Action: Applications to Health and Environment.